Interpolation of Fire Radiative Power in West Kalimantan using Ordinary Kriging - Fitriyana, Gita; Imro'ah, Nurfitri; Huda, Nur'ainul Miftahul; Zuleha, Zuleha (Universitas Muhammadiyah Mataram, 2025)
Forest fires are recurring environmental disasters with severe ecological and economic impacts, particularly in regions like West Kalimantan. One of the key indicators used to measure fire intensity is Fire Radiative Power (FRP). Accurate spatial prediction of FRP is essential to support early warning systems and mitigation strategies. This study is a quantitative descriptive research that applies a geostatistical spatial analysis technique, namely Ordinary Kriging interpolation, to predict FRP values in West Kalimantan for July, August, and September 2024. The data were obtained from satellite imagery (VIIRS NOAA-20), including latitude, longitude, and FRP values. Prior to modeling, data were tested for normality and found to follow a normal distribution. The spherical semivariogram model yielded the best fit for July and August with RMSE values of 0.046 and 0.011, respectively, while the Gaussian model was optimal for September (RMSE = 0.007). The results show spatial variation in FRP distribution across different regencies each month, with the highest estimated FRP values recorded in Kapuas Hulu (July: 63.56), Melawi (August: 69.00), and Ketapang (September: 55.27). Most areas demonstrated low fire intensity, as shown by the dominance of green zones on the prediction maps. However, localized red-yellow zones indicate areas with high fire potential, which shifted monthly. This study contributes by demonstrating the application of Ordinary Kriging in forest fire intensity mapping and highlights the importance of choosing an appropriate semivariogram model to enhance predictive accuracy. The resulting FRP prediction maps can serve as a valuable tool for policy planning and targeted fire prevention efforts.